A pilot histomorphology and hemodynamic of vasculogenic mimicry in gallbladder carcinomas in vivo and in vitro - Zhang Wen Z; Fan Yue Z; Sun Wei; Ge Chun Y (Journal of Experimental & Clinical Cancer Research, 2011)
Abstract Background Vasculogenic mimicry (VM), as a new blood supply for tumor growth and hematogenous metastases, has been recently described in highly aggressive human melanoma cells, etc. We previously reported VM in human gallbladder carcinomas and its clinical significance. In this study, we further studied histomorphology and hemodynamic of VM in gallbladder carcinomas in vivo and in vitro. Methods The invasive potential of human gallbladder carcinoma cell lines GBC-SD and SGC-996 were identified by Transwell membrane. The vasculogenic-like network structures and the signal intensities i.e. hemodynamic in gallbladder carcinomas stimulated via the three-dimensional matrix of GBC-SD or SGC-996 cells in vitro, the nude mouse xenografts of GBC-SD or SGC-996 cells in vivo were observed by immunohistochemistry (H&E staining and CD31-PAS double staining), electron microscopy and micro-MRA with HAS-Gd-DTPA, respectively. Results Highly aggressive GBC-SD or poorly aggressive SGC-996 cells preconditioned by highly aggressive GBC-SD cells could form patterned networks containing hollow matrix channels. 85.7% (6/7) of GBC-SD nude mouse xenografts existed the evidence of VM, 5.7% (17/300) channels contained red blood cells among these tumor cell-lined vasculatures. GBC-SD xenografts showed multiple high-intensity spots similar with the intensity observed at tumor marginal, a result consistent with pathological VM. Conclusions VM existed in gallbladder carcinomas by both three-dimensional matrix of highly aggressive GBC-SD or poorly aggressive SGC-996 cells preconditioned by highly aggressive GBC-SD cells in vitro and GBC-SD nude mouse xenografts in vivo.